Determination of the optimum frequency for Elaeis guineensis Jacq. detachment - Wan Ismail, Wan Ishak; Lam, Wai Yip; Razali, Mohd Hudzari (Academic Journals, 2011)
In Elaeis guineensis Jacq (oil palm) industry, fruit detachment and oil extraction of oil palm bunches are always being carried out in palm oil mill in a series of standard procedure. A lot of energy is needed and consumed throughout the procedure, especially during sterilization where a huge amount of energy is needed to produce pressurized steam in order to cook the fruit bunches, only to soften and weaken the stalk so as to facilitate the detachment of the fruits by threshing. This study was proposed to search for an alternative to this current practice. By developing a vibrational oil palm fruit detaching machine, fruitlets were detached from the bunch by means of vibration. The optimum vibration frequency for the detachment of fruitlets from the stalk was determined. On top of that, the use of ethephon hormone to loosen the fruitlets before they are detached from the bunch using the vibrational oil palm fruit detaching machine is also justified in this study. The designed and developed experimental vibrational oil palm fruit detaching machine was found to be able to detach fruitlets from the bunch when it is applied with vibration. Besides, the optimum frequency for the vibrational oil palm fruit detaching machine to detach the fruitlets from the bunch was determined to be 3.3 Hz. The use of ethephon hormone (Esigel) in this project has been justified that it has no side effect on the fruit components and moisture content of the oil palm bunches.